Prospective modelling of operational offshore wind farms on the distribution of marine megafauna in the southern North Sea - Virgili, Auriane; Laran, Sophie; Authier, Matthieu; Dorémus, Ghislain; Van Canneyt, Olivier; Spitz, Jérôme (Frontiers in Marine Science, 2024)
Intense development of Offshore Wind Farms (OWFs) has occurred in the North Sea with several more farms planned for the near future. These OWFs pose a threat to marine megafauna stressing the need to mitigate the impact of human activities. To help mitigate impacts, the Before After Gradient (BAG) design was proposed. We explored the use of the BAG method on megafauna sightings recorded at different distances from OWFs in the southern North Sea. We predicted intra-annual variability in species distribution, then correlated species distribution with the presence of operational OWFs and investigated the potential impact the operation of prospective OWFs may have on species distribution. Four patterns of intra-annual variability were predicted: species most abundant in spring, in winter, in both spring and winter, or all year round. We recommend that future OWF constructions be planned in summer and early fall to minimise impact on cetaceans and that offshore areas off northern France and Belgium be avoided to minimise impact on seabirds. Our prospective analysis predicted a decreased density for most species with the operation of prospective OWFs. Prospective approaches, using e.g. a BAG design, are paramount to inform species conservation as they can forecast the likely responses of megafauna to anthropogenic disturbances.